Frailty and outcomes of vascular access for hemodialysis – a scoping review - Lara R. Dias; Leandro Nóbrega; Tiago Costa-Pereira; Joana Ferreira; Armando Mansilha; Luís Coentrão (Angiologia e Cirurgia Vascular)
INTRODUCTION: Frailty is an age-related condition related to the decline of physiologic capacity and the increased vulnerability to stressors. It is associated with increased mortality, hospitalizations, and healthcare costs. Dialysis patients, due to age and comorbidities, are especially vulnerable to frailty. The aim of this review was to assess the impact of frailty on outcomes of vascular access for haemodialysis.